Validation of an instrument on motivation and attitude for the learning of legal and forensic dentistry in students of the ninth cycle of the School of Dentistry of the Private University of Tacna. 2017. - Núñez Cárdenas, José Elard (2019)
This work mentions the process of developing an instrument that was validated to measure the motivation and attitudes of students in the undergraduate course of Legal and Forensic Dentistry that is taught in the Professional School of Dentistry. The instrument was applied in an experimental group of 46 students. The instrument has two parts, the first is a motivation test and the second part an attitude test both under the Likert mode. The instrument was adjusted by expert judgment and by contrasting reliability and consistency of Cronbach's alpha, reaching a value of 0.8. With this analysis, it is confirmed that the questionnaire is congruent and tests its consistencies for internal reliability, to be applied and adapted to other subjects.